2015
DOI: 10.2320/matertrans.m2014384
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Passive Films on Ni-Based Alloys in Acidic and Neutral Solutions

Abstract: The present work reports the structure, chemical composition and electronic properties of passive films formed on Alloy 600 and Alloy 690 in borate buffer and sulfuric acid solutions. Photoelectrochemical response from passive films varied depending on the alloy substrates and the solutions. XPS analysis revealed that the passive films formed on Alloy 600 and Alloy 690 consisted of an outer hydroxide layer and an inner oxide layer in the borate buffer solution as well as the sulfuric acid solution. The chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…35 It is worth mentioning that in this potential range, Ni remains in a passive state. 36,37 Similar polarization curves were obtained for the ternary Ni-xCr-8Fe alloys (x = 14, 22, 30 wt%), as presented in Fig. 3b.…”
Section: Obtaining Way Parameterssupporting
confidence: 78%
“…35 It is worth mentioning that in this potential range, Ni remains in a passive state. 36,37 Similar polarization curves were obtained for the ternary Ni-xCr-8Fe alloys (x = 14, 22, 30 wt%), as presented in Fig. 3b.…”
Section: Obtaining Way Parameterssupporting
confidence: 78%
“…This approach is similar to the duplex-structure analysis described in our previous studies on passive films of Fe-Cr alloys, Ni-Cr alloys and Cr. 11,13,23,28,29 The E g s of the passive film on Cr were estimated as approximately 2.5 and 3.6 eV. Referring to E g reported for Cr oxide and hydroxide, 13,30 it is found that the E g s of 2.5 and 3.6 eV obtained from the photoelectrochemical response were attributed to the outer Cr(OH) 3 and inner Cr 2 O 3 layers, respectively.…”
Section: Hv Imentioning
confidence: 89%
“…[3][4][5] Passive films on Fe-Cr, Ni-Cr and Co-Cr-Mo alloys consist of oxides and hydroxides, including large amounts of Cr. [6][7][8][9][10][11] Passive films on Ti 12 and Cr 13 are known to exhibit semiconductive behavior. Ti oxides are widely used as functional materials in light-energy conversion devices and their semiconductor behavior has been investigated in various studies, including the pioneering work of Bard.…”
mentioning
confidence: 99%
See 1 more Smart Citation